2012
DOI: 10.1111/j.1551-2916.2012.05445.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Domain Size on Local d33 in Tetragonal (Na0.53K0.45Li0.02)(Nb0.8Ta0.2)O3 Ceramics

Abstract: Lead‐free (Na0.53K0.45Li0.02)(Nb0.8Ta0.2)O3 (NKLNT) was prepared using a conventional cold‐pressing method. A commercial piezoresponse force microscope (PFM) was applied to observe the domain structures of NKLNT ceramics. The typical configuration of the ferroelectric domain was analyzed in abnormal grains with grain sizes that exceeded 40 μm, where tetragonal 90° domains are predominant. The local piezoresponse hysteresis loops were characterized and studied as a function of the domain width (dw) in the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…The piezoelectric response of fibers depends on the applied voltage and diameter of the fibers. 53 The most important parameters influencing the diameter of the fiber are solution viscosity, temperature, surface tension, and distance between the tip and the collector. 54 Le et al found that the piezoelectric coefficient of piezoelectric materials increases with decrease in the domain size.…”
Section: Resultsmentioning
confidence: 99%
“…The piezoelectric response of fibers depends on the applied voltage and diameter of the fibers. 53 The most important parameters influencing the diameter of the fiber are solution viscosity, temperature, surface tension, and distance between the tip and the collector. 54 Le et al found that the piezoelectric coefficient of piezoelectric materials increases with decrease in the domain size.…”
Section: Resultsmentioning
confidence: 99%
“…38,39 The apparatus PFM facilitates the in situ domain morphology observations at different temperatures by providing evidence of domains orientation. 38,39 The apparatus PFM facilitates the in situ domain morphology observations at different temperatures by providing evidence of domains orientation.…”
Section: Resultsmentioning
confidence: 99%
“…The piezoelectric performance of ferroelectric polycrystals is deemed to be highly correlated with domain morphologies. 38,39 The apparatus PFM facilitates the in situ domain morphology observations at different temperatures by providing evidence of domains orientation. 11,21,40,41 The in situ lateral PFM phase and lateral piezoresponse of the x = 0 and x = 0.5 samples at different temperatures are depicted in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Cho et al . found that local d 33 * increased from 18 to 38 pm/V with decrease in domain size from 1000 to 300 nm in (Na 0.53 K 0.45 Li 0.02 )(Nb 0.8 Ta 0.2 )O 3 . Therefore, it is reasonable to hypothesize, that ultrahigh strain could be obtained with the miniaturization of the domain structure down to the nanometer scale (nanodomain) in KNN‐based piezoceramics.…”
Section: Introductionmentioning
confidence: 97%